Teachers’ Beliefs about Communicative Language Teaching (CLT) and the Implementation in Classroom Practices - Trifita Setyaningrum (Jurnal Pendidikan Humaniora, 2018)
Abstract: This study aims at investigating the match between beliefs and classroom practices about communicative language teaching (CLT). Survey design through questionnaire for professional teachers of English and guided interviews is employed in this study. The 25 questionnaire items revealed the teachers’ belief about CLT and the classroom practices based on its characteristics, i.e.: overall goals, relationship of form and function, fluency-accuracy, focus on real-world contexts, autonomy and strategic involvement, teacher roles, and student roles. The data were gathered, reduced, grouped, and verified. The results showed that the highest discrepancy is on the aspect of fluency-accuracy.Key Words: teacher’s belief, communicative language teaching, classroom practicesAbstrak: Penelitian ini menganalisa kesesuaian antara kepercayaan terhadap pembelajaran komunikatif (CLT) dan penerapannya. Data diperoleh melalui survei dengan kuesioner yang ditujukan kepada guru Bahasa Inggris profesional dan interview sebagai konfirmasi. 25 pernyataan kuesioner menunjukkan kepercayaan guru terhadap pembelajaran komunikatif dan penerapannya di dalam proses pembelajaran. Kuesioner ini disusun berdasarkan 7 karakteristik pembelajaran komunikatif: tujuan menyeluruh, hubungan bentuk dan fungsi Bahasa, ketepatan dan kelancaran, penerapan di dunia nyata, keterlibatan dan strategi belajar individu, peran guru, dan peran siswa. Data yang terkumpul dikelompokkan dan dicocokkan. Hasil penelitian ini menunjukkan bahwa ketidaksesuaian penerapan prinsip CLT dalam proses pembelajaran terutama dalam aspek ketepatan dan kelancaran.Kata kunci: keyakinan guru, pembelajaran komunikatif, praktik kelas